Effect of low glyphosate doses on flowering and seed germination of glyphosate-resistant and -susceptible Digitaria insularis - Anunciato, Vitor M [UNESP] (2022)
BACKGROUND: Herbicide hormesis is characterized by stimulation of various growth and developmental parameters, such as biomass and height, at low herbicide doses. Other possible hormetic effects are earlier flowering, higher seed weight, more seeds, and a shorter plant life cycle, which could favor the propagation of the species. This study tested the early flowering in glyphosate-resistant and -susceptible Digitaria insularis biotypes under treatment with low glyphosate doses. RESULTS: Hormesis caused by low glyphosate doses occurred in all experiments. The hormetic effects were a decrease in time necessary for the formation of inflorescences and increased seed weight and germination speed. Higher glyphosate doses were required for the hormetic effect in the glyphosate-resistant than the -susceptible D. insularis biotype. CONCLUSIONS: Hormesis caused by low glyphosate doses in D. insularis may provide an advantage for the dissemination of this species, helping to alter the weed flora. As the doses that cause stimulation in glyphosate-resistant biotypes are higher than in glyphosate-susceptible biotypes, the selection of resistant biotypes may be favored in glyphosate-sprayed fields, increasing the rate of infestation of glyphosate-resistant biotypes.